Resistivity borehole logging data of MeBo sediment core GeoB22620-1 - Tim Freudenthal (PANGAEA, 2020)
Logging was performed with the sea floor drill rig MARUM-MeBo200 in a borehole drilled with a 103 mm diameter bit. The 1185 Slimhole Dual Induction instrument developed by ANTARES Datasystems GmbH was used. The probe was deployed in the memory mode with the logging string being inserted into the drill string and the sensors located below the drill bit. The measurement was conducted as upcast while the drill string was pulled back to the seafloor out of the borehole. Data processing was conducted using the Antares Software GeoBase 5.92. The trip out speed was about 1 cm/s and the logging frequency was 0.5 Hz. The probe provides both deep and medium investigation induction conductivity curves and calculated resistivity Rdeep and Rmedium. The investigation depth is 1.3 m for deep and 0.65 m for medium resistivity. The vertical resolution is approximately 0.8 m and the measuring range is 0.5 – 100 ohmm. The maximum error is about 5% for low resistivity values and about 25 % at the high range.